2017
DOI: 10.1136/esmoopen-2016-000150
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-infiltrating lymphocytes are correlated with higher expression levels of PD-1 and PD-L1 in early breast cancer

Abstract: BackgroundThe presence of tumour-infiltrating lymphocytes (TILs) is a favourable prognostic factor in patients with early breast cancer. Programmed cell death-1 (PD-1) and its ligand PD-L1 are associated with a variety of adverse features. The purpose of this study was to clarify the relationships between TILs, PD-1 and PD-L1 as well as their prognostic implications in early breast cancer.MethodsWe investigated 180 patients with breast cancer who received neoadjuvant chemotherapy and underwent subsequent surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 33 publications
17
88
2
Order By: Relevance
“…It can be caused by infiltrating immune cells producing factors driving PD‐L1 expression . Previous studies have also shown that TILs are correlated with higher expression levels of PD‐L1 expression in breast and lung cancers …”
Section: Discussionmentioning
confidence: 99%
“…It can be caused by infiltrating immune cells producing factors driving PD‐L1 expression . Previous studies have also shown that TILs are correlated with higher expression levels of PD‐L1 expression in breast and lung cancers …”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated PD‐L1 expression according to baseline clinicopathological features of patients with BC, consistently reporting a correlation between higher PD‐L1 expression and unfavorable classic prognostic factors, particularly poorer histological grade , higher proliferative index , more advanced N stage , larger tumor size , and younger age at BC diagnosis .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies evaluate the importance of PD-1/PD-L1 expression on tumor cells and/or immune cells and the presence of TILs and Tregs in the tumor microenvironment in predicting response to treatment pertaining to BC [3,104,108,113,114]. Specifically, blocking immune evasion and attracting more TILs and fewer Tregs (reactivating immunogenicity of BC) to the tumor microenvironment can improve the OS of BC patients [19,23,[115][116][117][118][119]. Sixteen percent of HER2 + subtypes are lymphocyte predominant (> 50-60% of TILs present) and are associated with improved outcome (EFS: event-free survival, OS) with many treatment modalities [19,[120][121][122][123][124].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
“…Moreover, based on 6 different studies, in [130], the authors highlight that PD-L1 expression in both tumor cells and immune cells of the host can contribute to the overall response to treatment. Hence, the evaluation of an overall expression in both these cells is recommended as a predictive biomarker [23,[115][116][117][118][119].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%